2019
DOI: 10.1007/s10329-019-00755-8
|View full text |Cite
|
Sign up to set email alerts
|

Longevity and mortality of captive chimpanzees in Japan from 1921 to 2018

Abstract: Utilizing the Great Ape Information Network (GAIN), an open-access nationwide database containing the detailed life history information of all apes who have lived or currently reside in Japan, we present a robust chimpanzee life table by single year of age and sex including 821 individuals spanning nearly a century, current through March 11, 2019. While the demographic composition and status of captive chimpanzees in Japan has been previously reported, longevity and mortality statistics have not. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 30 publications
3
45
0
1
Order By: Relevance
“…Chimpanzees are one of humans' closest living relatives and have been studied for decades, which has allowed for the comparison of life history patterns to shed light on human evolution (e.g., Hawkes, Smith & Robson, 2009;Hill et al, 2001;Muller & Wrangham, 2014;Thompson et al, 2007;Wood et al, 2017;Davison & Gurven, 2021). Life expectancy at birth for hunter-gatherers ranges from 21-37 years across groups and between 26-43% of people survive to age 45 (Gurven & Kaplan, 2007), similar to what has been found in a wild (Wood et al, 2017) and a captive chimpanzee population (Havercamp et al, 2019). The average life expectancy of wild chimpanzees varies across populations (Table 1).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Chimpanzees are one of humans' closest living relatives and have been studied for decades, which has allowed for the comparison of life history patterns to shed light on human evolution (e.g., Hawkes, Smith & Robson, 2009;Hill et al, 2001;Muller & Wrangham, 2014;Thompson et al, 2007;Wood et al, 2017;Davison & Gurven, 2021). Life expectancy at birth for hunter-gatherers ranges from 21-37 years across groups and between 26-43% of people survive to age 45 (Gurven & Kaplan, 2007), similar to what has been found in a wild (Wood et al, 2017) and a captive chimpanzee population (Havercamp et al, 2019). The average life expectancy of wild chimpanzees varies across populations (Table 1).…”
Section: Introductionmentioning
confidence: 83%
“…In Kanyawara in East Africa, adult chimpanzees (14 y) can expect to live 38 years (Muller & Wrangham, 2014) and at Ngogo, also in East Africa, 43 years (Wood et al, 2017). In captivity in Japan, a 14-year old individual is expected to reach 42 years of age (Havercamp et al, 2019). Longevity estimates of chimpanzees from birth are lower due to the high risk infant period, from 13 years across five sites (Hill et al, 2001), 19 years at Kanyawara (Muller & Wrangham, 2014), 28 years in captivity (Havercamp et al, 2019), to 33 years at Ngogo (Wood et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One case study even describes blood transfusions to treat an anaemic chimpanzee at Tchimpounga [255]. Post-mortem reports from chimpanzees who died at GFAS-accredited sanctuaries have been reviewed [256], while longevity and mortality of captive chimpanzees in Japan, including at Kumamoto, has also been studied [257].…”
Section: (C) Veterinary Genetic and Physiologymentioning
confidence: 99%
“…Since neurodegenerative diseases such as Alzheimer's disease (AD) and Parkinson's disease are increasing year by year, knowledge of age-related neuropathology in apes such as chimpanzees contributes to understanding human pathology. In this study, the oldest chimpanzee reported so far has been analyzed pathologically, 1 and its brain lesions were compared to previously reported neurodegenerative diseases in animals or humans.…”
mentioning
confidence: 99%